Nationwide survey on the current practice of ventricular tachycardia ablation. Issue 9 (September 2019) - Vergara, Pasquale; Casella, Michela; Barbato, Gaetano; De Ruvo, Ermenegildo; Grandinetti, Giuseppe; Notarstefano, Pasquale; Tola, Gianfranco; Calvi, Valeria; Santini, Luca; Nissardi, Vincenzo; Nonis, Alessandro; Ricci, Renato P.; et al.
Abstract : Methods: We performed a nationwide survey on the current practice of ventricular tachycardia catheter ablation in Italy during the year 2016. Results: Among 145 operators participating in the survey, 58 (40.0%) did not perform any ventricular tachycardia ablation in 2016. Among those performing ventricular tachycardia ablation, 9 operators (6.2%) performed only right ventricular endocardial catheter ablation, 52 (35.9%) performed endocardial catheter ablation both in the right and left ventricle (LV) and 26 (17.9%) performed both endocardial and epicardial LV catheter ablations. Seventy operators (89.7%) among the 78 performing LV and epicardial ablations treated patients with ischemic cardiomyopathy; ablations in the setting of other causes were less frequently performed. The following were considered as minimum requirements for ventricular tachycardia ablation: presence of a three-dimensional mapping system (120 operators, 82.8%), ICU in the hospital (118 operators, 81.4%), operator's training in high volume centers (93 operators, 64.1%). Twenty-eight operators (19.3%) performed catheter ablation in patients with electrical storm only after hemodynamic stabilization, 41 operators (28.3%) also during the acute phase and 9 operators (6.2%) never performed catheter ablation in electrical storm patients; the remaining 67 operators did not perform ventricular tachycardia ablation at all, or performed ablations only in the right ventricle. Conclusion: The present survey provides a snapshot of the current invasive treatment of ventricular tachycardia by catheter ablation. The procedure, especially in the setting of ischemic cardiomyopathy, is performed nationwide. Complex cases, including those with electrical storm, should be managed within a preestablished integrated network of regional referral centers able to transfer patients as soon as possible.